Rocky Mountain advanced computing consortium cyberinfrastructure plan - Hauser, Thomas, author; Burns, Patrick J., author; Cheatham, Thomas E., author; Siegel, H. J., author; Williams, James, author (Colorado State University. Libraries, 2017)
The Rocky Mountain Advanced Computing Consortium (RMACC) is a collaboration among academic and research institutions located throughout the intermountain region. Our mission is to facilitate widespread effective use of cyberinfrastructure throughout the region by: Educating graduate and undergraduate students, faculty, researchers, facilitators, and industry partners on the use of computational science, high performance computing, advanced networking, virtualization, and data management; Coordinating multi-institutional efforts to advance research, practice, and education in computational science in order to address important regional problems; Bringing together a broad range of research computing staff, researchers, faculty, and industry partners with a depth of experience and expertise not available at any single institution and facilitate their collaboration in multi-disciplinary and multi-institutional teams. Since advancing the regional cyberinfrastructure is part of the goal of the consortium, RMACC institutions are focused on improving the regional cyberinfrastructure, especially people, networking, shared compute and data resources going forward.
Keywords: cyberinfrastructure